KNOWLEDGE OF ENTERPRISE AS A TOOL FOR BUSINESS PROCESS OPTIMIZATION USING MARKETING ACTIVITIES - Recicar, Jakub; Tomlain, Juraj (European Scientific Journal, ESJ, 2014)
Knowledge as one of the most valuable forms of corporate capital during the current crisis seems to be a very effective tool. Effectiveness lies in its ability to transform raw data, statistics, pictures and another type of information into usable forms of knowledge. This is useful particularly in business processes, where this knowledge as one of the production factors can significantly impact on business results. Proper continuous management (creation, sharing, storage, processing, and exploitation) knowledge is one of the necessary conditions of competitiveness among firms that have worked with knowledge actively. They are found in various forms as either in the form of data in databases or as the partial result of their employees in project information systems. Selected questions from the corporate sector were examined in the author’s empirical research. In research were demonstrated attitudes of selected SMEs in the manufacturing of chemical, pharmaceutical and food technology. Acknowledgement: This publication has been prepared as a partial output in the research project ref. no.: 1/0055/13, VEGA No. 13 Commission for Economic and Legal Sciences - Project title: Systemization impact factors and conditions of knowledge management in the context of business strategy on work motivation and its reflection in growth of efficiency, respectively sustainable levels of business.